Mother, researcher, feminist, woman: reflections on "maternal status" as a researcher identity. (8th July 2014) - Frost, Nollaig; Holt, Amanda
Abstract : Purpose: – The purpose of this paper is to discuss the ways in which a researcher's maternal status as "mother" or "non-mother/child-free" is implicated in the research process. Design/methodology/approach: – This paper draws on the experiences as two feminist researchers who each independently researched experiences of motherhood: one as a "mother" and one as a "non-mother/child-free". The paper draws on extracts from the original interview data and research diaries to reflect on how research topic, methodology and interview practice are shaped by a researcher's maternal status. Findings: – The paper found that the own maternal identities shaped the research process in a number of ways: it directed the research topic and access to research participants; it drove the method of data collection and analysis and it shaped how the authors interacted with the participants in the interview setting, notably through the performance of maternal identity. The paper concludes by examining how pervasive discourses of "good motherhood" are both challenged and reproduced by a researcher's maternal status and question the implications of this for feminist research. Originality/value: – While much has been written about researcher "positionality" and the impact of researcher identity on the research process, the ways in which a researcher's "maternal status" is implicated in the research process has been left largely unexamined. Yet, as this paper highlights, the interaction of the often-conflicting identities of "mother", "researcher", "feminist" and "woman" may shape the research process in subtle yet profound ways, raising important questions about the limits of what feminist social research about "motherhood" can achieve.